Eyes on the Universe : the Story of the Telescope - Moore, Patrick (Springer London : Imprint : Springer, 1997)
Eyes on the Universe is an illustrated history of the telescope, beginning with pre-telescopic observatories and the refractors of Galileo, Lippershey and Digges, and ending with the most modern instruments including - of course - the Hubble Space Telescope. Written by Dr Patrick Moore CBE, to celebrate the 40th Anniversary of the world's longest-running television programme, the BBC's The Sky at Night, the book takes an enthusiastic look at the development of astronomical telescopes. It provides its readers with a fascinating overview of the way astronomical telescopes have evolved with technology during the past 450 years. Amateur and professional astronomers alike will find this book both entertaining and instructive.